A probiotic mix partially protects against castration-induced bone loss in male mice. Issue 2 (23rd June 2022) - Lawenius, Lina; Colldén, Hannah; Horkeby, Karin; Wu, Jianyao; Grahnemo, Louise; Vandenput, Liesbeth; Ohlsson, Claes; Sjögren, Klara
Abstract : Studies in postmenopausal women and ovariectomized mice show that the probiotic mix Lacticaseibacillus paracasei DSM13434, Lactiplantibacillus plantarum DSM 15312 and DSM 15313 ( L. Mix) can protect from bone loss caused by sex steroid deficiency. Whether probiotic bacteria can protect bone also in sex steroid-deficient males is less studied. We used the orchiectomized mouse as a model for age-dependent bone loss caused by decreasing sex hormone levels in males. We treated 10-week-old male mice with either vehicle (veh) or L. Mix for 6 weeks, starting 2 weeks before orchiectomy (orx) or sham surgery. Importantly, mice treated with L . Mix had a general increase in total body bone mineral density (BMD) and lean mass ( P ≤ 0.05) compared with veh-treated mice. Detailed computer tomography analysis of dissected bones showed increased trabecular BMD of the distal metaphyseal region of the femur in L . Mix compared to veh-treated orx mice (+8.0%, P ≤ 0.05). In the vertebra, L . Mix treatment increased trabecular bone volume fraction BV/TV (+11.5%, P ≤ 0.05) compared to veh in orx mice. Also, L . Mix increased the levels of short-chain fatty acids (SCFAs) such as propionate and acetate and important intermediates in SCFA synthesis such as succinate and lactate in the cecal content of male mice. In conclusion, L . Mix treatment resulted in a general increase in BMD in adult male mice and prevented trabecular bone loss in femur and vertebra of orx mice. These bone protective effects of L . Mix were associated with increased levels of SCFAs in the cecal content of male mice.